2012
DOI: 10.1007/s13225-012-0199-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of nivicolous myxomycetes of the Teberda State Biosphere Reserve (Northwestern Caucasus, Russia)

Abstract: Nivicolous myxomycete assemblages were surveyed on the northwest of the Greater Caucasian ridge in May-June 2010 and 2011 at a north facing transect between 1,700 and 2,920 m elevation of the summit Malaya Khatipara situated within the Teberda State Biosphere Reserve. Morphological characters of 396 collections representing 45 taxa (39 species, 3 varieties, and 3 forms) of myxomycetes in 8 genera and 5 families were recorded. Many (13) taxa are classified as rare (a species represents <0.5 % of all records). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Research of Fiore-Donno et al [12], supported this idea, indicating that delimitation of M. carestiae, M. cribrarioides, and M. aggregatum seems to correlate with phylogenetic analysis based on the SSU sequences. As well established, molecular analysis provides a promising methodology to clarify as well as verify taxonomic positions of many genera and species [12,13]. This combinational approach could successfully resolve taxonomic problems and properly indicate inter-and intraspecific variability within this group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research of Fiore-Donno et al [12], supported this idea, indicating that delimitation of M. carestiae, M. cribrarioides, and M. aggregatum seems to correlate with phylogenetic analysis based on the SSU sequences. As well established, molecular analysis provides a promising methodology to clarify as well as verify taxonomic positions of many genera and species [12,13]. This combinational approach could successfully resolve taxonomic problems and properly indicate inter-and intraspecific variability within this group.…”
Section: Discussionmentioning
confidence: 99%
“…All so far recognized Meriderma species are present mainly in Europe, the Alps [1,14]. Six of them have recently been reported from the Caucasus [13] and five from the Khibiny Mountains [25]. Three species, M. aggregatum, M. carestiae, and M. spinulosporum are known from the Andes in South America [23], however, the first and the last slightly deviating in spore ornamentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary problem is the difficulty of isolating DNA from sporophores without cross-contamination. Although DNA isolation from a single sporophore (Martín et al, 2003) and use of only mature and distantly separated colonies of myxomycetes (Novozhilov et al, 2013) were reported to be successful in eliminating cross-contamination, the universal DNA databases are dominated by rDNA sequences from 7 different genera of myxomycetes. This is why it is very challenging to develop primers by using published sequence data from conserved rDNA genes of related myxomycetes species.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize cross‐contamination, the precautions described in Novozhilov et al. () were applied during sampling and isolation of the sporocarps. DNA was extracted according to manufacturer's protocol by either the Stratec Invisorb Spin Plant Mini Kit (Berlin, Germany), the Qiagen Plant kit (Hilden, Germany) or OMEGA Plant Kit (Norcross, Georgia, USA).…”
Section: Methodsmentioning
confidence: 99%